2013
DOI: 10.1590/s1413-78522013000200010
|View full text |Cite
|
Sign up to set email alerts
|

Conceitos atuais em osteoartrite

Abstract: Osteoarthritis (OA), the most common form of joint disease, affects mainly the hips, knees, hands and feet, leading to severe disability and loss of quality of life, particularly in the elderly population. Its importance grows every year with the aging of the population, with a large increase in the elderly population compared to younger patients. The progressive understanding of the pathophysiology of OA, the perception that the process is not purely mechanical and / or aging, and clarification of the inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 30 publications
1
42
0
10
Order By: Relevance
“…De maneira similar a este trabalho, outros estudos também encontraram associação entre a IU e o relato de artrite, artrose e reumatismo entre as mulheres idosas 26,32 . A osteoartrose é descrita como a doença articular mais comum, especialmente entre indivíduos idosos 33 . Trata-se de uma doença multifatorial que, em alguns casos, pode levar à incapacidade funcional significativa.…”
Section: ▄ Resultadosunclassified
“…De maneira similar a este trabalho, outros estudos também encontraram associação entre a IU e o relato de artrite, artrose e reumatismo entre as mulheres idosas 26,32 . A osteoartrose é descrita como a doença articular mais comum, especialmente entre indivíduos idosos 33 . Trata-se de uma doença multifatorial que, em alguns casos, pode levar à incapacidade funcional significativa.…”
Section: ▄ Resultadosunclassified
“…Various studies have demonstrated that the loss of QOL of a person with knee osteoarthritis may be a direct consequence of reduced mobility, increased pain, muscle imbalance and restriction of overall functionality589). However, few studies have sought to determine the impact of a patient's general functional independence (FI) on the general health-related QOL in this important chronic disease910).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis presents a clinical picture of mechanically characteristic pain and symptoms which may oscillate over time according to the physical effort performed by the individual [23]. Pain may occur with less intense activities as the disease progresses [24,25]. The presence of depressive symptoms associated with low back pain is a warning sign because of its impact on physical function, independence and quality of life.…”
Section: Discussionmentioning
confidence: 99%